Peer Conformity and Its Link to Bullying Among Upper Elementary Students: Konformitas Teman Sebaya dan Kaitannya dengan Perundungan di Kalangan Siswa Sekolah Dasar Kelas Atas - Rachmawati, Henny; Laili, Nurfi (Universitas Muhammadiyah Sidoarjo, 2025)
Bullying refers to acts of violence perpetrated by individuals or groups that are seen as